La concezione della tecnica nel discorso ambientalista del Club di Roma - Musso, Alberto (Filosofia, 2016)
One of the most important characteristics of modern environmentalism is the attention to technology, the human activity that is blamed the most for Nature’s degradation. In the disputes among environmentalists, reference is often made to The Limits to Growth, a 1972 seminal work edited by Meadows. This well-known technical-scientific study, commissioned by The Club of Rome, uses the then-innovative computer methodology of System Dynamics, which illustrates the existence and the proximity of physical limits to material growth by means of graphs and charts. Starting from an analysis of The Limits to Growth, this essay attempts to underline the link between the various interpretations of the ensuing data, and the different conceptions of technology and technological society. For better comprehension purposes, the present essay reports the discussions of The Club of Rome and the thoughts of Aurelio Peccei, the club’s founder.